2021
DOI: 10.1158/2159-8290.cd-20-1540
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CDK4/6 Promotes CD8 T-cell Memory Formation

Abstract: CDK4/6 inhibitors are approved to treat breast cancer and are in trials for other malignancies.We examined CDK4/6 inhibition in mouse and human CD8 T cells during early stages of activation. Mice receiving tumor-specific CD8 T cells treated with CDK4/6 inhibitors displayed increased T cell persistence and immunologic memory. CDK4/6 inhibition upregulated Mxd4, a negative regulator of Myc, in both mouse and human CD8 T cells. Silencing of Mxd4 or Myc in mouse CD8 T cells demonstrated the importance of this axis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 59 publications
6
74
3
Order By: Relevance
“…Moreover, it was previously reported that the amount of MYC protein is greater in CD8 + than in CD4 + T lymphocytes (Marchingo et al, 2020), suggesting that CD8 + T cells would be more sensitive to Myc deletion. Conversely to our result, a recent study (Heckler et al, 2021) shows that MYC inhibition (using Palbociclib, a CDK4/6 inhibitor) promotes CD8 T cell memory formation. This contrasting observation can be explained by the fact that in Heckler et al paper only the MYC-MAX function is affected, thus some MYC functions independent of MAX, such as the transcription of RNA polymerase III targets, are not impacted (van Riggelen et al, 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, it was previously reported that the amount of MYC protein is greater in CD8 + than in CD4 + T lymphocytes (Marchingo et al, 2020), suggesting that CD8 + T cells would be more sensitive to Myc deletion. Conversely to our result, a recent study (Heckler et al, 2021) shows that MYC inhibition (using Palbociclib, a CDK4/6 inhibitor) promotes CD8 T cell memory formation. This contrasting observation can be explained by the fact that in Heckler et al paper only the MYC-MAX function is affected, thus some MYC functions independent of MAX, such as the transcription of RNA polymerase III targets, are not impacted (van Riggelen et al, 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…This is attributable, at least in part, to inhibition of CDK6-mediated phosphorylation of nuclear factor of activated T cells (NFAT) transcription factors [ 78 , 81 ]. Most recently, CDK4/6i has also been demonstrated to promote differentiation of CD8 T cells toward a memory cell fate, which might contribute to enhanced anti-tumor efficacy [ 83 , 84 ]. Data on whether this memory differentiation effect in CD8 T cells is RB-dependent are mixed.…”
Section: Mechanisms Of Action Of Cdk4/6 Inhibition In Breast Cancer: ...mentioning
confidence: 99%
“…It triggers tumor inhibition through regulation of ULF-dependent p19Arf ubiquitylation ( 47 ). CDK4/6 inhibitor upregulates MXD4 expression that negatively modulates MYC in CD8+ T cells ( 48 ). NR1H2 modulates cholesterol homeostasis within human cells, controlling fitness and function of activated T cells ( 49 ).…”
Section: Discussionmentioning
confidence: 99%